2005
DOI: 10.1111/j.0023-8333.2005.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

“Task” as Research Construct

Abstract: The article examines “task” as research construct as predominantly conceived in terms of task‐as‐workplan in the task‐based learning/second language acquisition literature. It is suggested that “task” has weak construct validity and ontology in an overwhelmingly quantitative paradigm because the construct has a “split personality.” Conceptualization is based on the task‐as‐workplan, but data are gathered from the task‐in‐process. The article adopts a conversation analysis perspective and demonstrates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(87 citation statements)
references
References 31 publications
3
79
0
2
Order By: Relevance
“…Coughlan and Duff (1994), drawing on the tenets of sociocultural theory, showed that the ‘activity’ that results from a focused ‘task’ varied from learner to learner and also from performance to performance of the task by the same learner. Seedhouse (2005) argued that the discrepancy between the predicted and actual language use resulting from a task was so great that a task could only be defined in terms of the language processes that resulted from its performance, and that therefore it was impossible to plan a language course based on tasks‐as‐workplans. The problem becomes even more acute with focused tasks.…”
Section: Misunderstandings About Tbltmentioning
confidence: 99%
See 1 more Smart Citation
“…Coughlan and Duff (1994), drawing on the tenets of sociocultural theory, showed that the ‘activity’ that results from a focused ‘task’ varied from learner to learner and also from performance to performance of the task by the same learner. Seedhouse (2005) argued that the discrepancy between the predicted and actual language use resulting from a task was so great that a task could only be defined in terms of the language processes that resulted from its performance, and that therefore it was impossible to plan a language course based on tasks‐as‐workplans. The problem becomes even more acute with focused tasks.…”
Section: Misunderstandings About Tbltmentioning
confidence: 99%
“…Foremost among these critics are Sheen (1994; 2004) and Swan (2005). Other critics include Seedhouse (1999 and 2005), who has challenged TBLT on the grounds that ‘task’ does not constitute a valid construct around which to build a language teaching programme, and Widdowson (2003), who has argued that the criteria for defining tasks are overly loose and that TBLT over emphasizes ‘authentic’ language use.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis on students' communicative competence; a focus on meaning rather than form; an (intended) aim to replicate language outside the classroom; and, in particular, "conversation," however, is criticized by, for instance, Seedhouse (1996) and others for being considered as a pedagogical concept, rather than being based on communicative or sociolinguistic theory. Similarly, task-based instruction (e.g., Foster & Skehan, 1996;Skehan, 1999Skehan, , 2003 is supposed to stimulate specific types of language (Nunan, 1989, p. 45), and is, therefore, an intended pedagogical methodology (see also Seedhouse, 1999Seedhouse, , 2005.…”
Section: Second Language Teachingmentioning
confidence: 99%
“…In line with the scope of the current paper, taskoriented interactional settings were investigated by a number of CA-for-SLA researchers (Hellerman, 2008;Hellerman & Pekarek Doehler, 2010;Markee & Kunitz, 2013;Mondada & Pekarek Doehler, 2004;Mori, 2002;Seedhouse, 1999Seedhouse, , 2005Seedhouse & Almutairi, 2009;Kunitz & Skogmyr-Marian, 2017). All of these studies present descriptions of contextspecific interactional achievements oriented to pedagogical tasks at hand.…”
Section: Literature Reviewmentioning
confidence: 96%